2003
DOI: 10.1007/s10286-003-1120-4
|View full text |Cite
|
Sign up to set email alerts
|

Variations in dynamic lung compliance during endoscopic thoracic sympathectomy with CO 2 insufflation

Abstract: Endoscopic thoracic sympathectomy (ETS) is the preferred surgery for treatment of intractable palmar hyperhidrosis (PH). General anesthesia with onelung collapsed ventilation (OLCV) using single-lumen tracheal tube (SLT), is our preferred anesthetic technique for ETS. Intrapleural CO(2) insufflation (capnothorax) was used to ensure lung collapse. The current study examined the effects of capnothorax on dynamic lung compliance (DLC) of the ventilated lung during ETS. After obtaining written informed consent, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The impact of CO 2 insufflation on the respiratory system has also been studied. El-Dawlatly et al [23] reported a significant pressure-dependent increase in peak airway pressure and a decrease in dynamic lung compliance but no difference in tidal volume or minute ventilation during volume-controlled ventilation.…”
Section: Carbon Dioxide Insufflation During Robotic Surgerymentioning
confidence: 99%
“…The impact of CO 2 insufflation on the respiratory system has also been studied. El-Dawlatly et al [23] reported a significant pressure-dependent increase in peak airway pressure and a decrease in dynamic lung compliance but no difference in tidal volume or minute ventilation during volume-controlled ventilation.…”
Section: Carbon Dioxide Insufflation During Robotic Surgerymentioning
confidence: 99%
“…That technique we have described validated some time ago for patients undergoing thoracoscopic sympathectomy for the treatment of palmar hyperhidrosis. [345] In case lung isolation is required, we have described the tools which could be used and we divided them into the double-lumen tube (DLT) and bronchial blocker (BB). DLT was further classified into two types according to the material used for their manufacture into polyvinyl chloride and silicone types.…”
mentioning
confidence: 99%